PERAN PEREMPUAN DALAM DUNIA PENDIDIKAN PERSPEKTIF HAMKA - Made Saihu; Abd Aziz (STIT AL-AMIN KREO TANGERANG, 2023)
This study aims to make women more aware of their role as social beings. Most among women only know their role as housewives, but many education experts consider this to be incorrect because women have a major role in education. Prophet Muhammad, once said that the first upbringing of a child lies in a mother. This role was once played by a hero mobilizing education for a woman, namely R.A Kartini, who rebelled against the ignorance experienced by women. In addition, Hamka has the perspective that the role of women greatly influences one's success. Therefore, this thesis, entitled The Role of Women in Hamka Education, uses the library search method. By using the library search research method, this research is classified as Library Research (library research) with qualitative descriptive analysis techniques by collecting data or materials related to the theme of discussion and problems taken from library sources